ANALISIS SISTEM INFORMASI AKUNTANSI DAN EFEKTIVITAS PENGAMBILAN KEPUTUSAN TERHADAP KINERJA UMKM DI DESA PEMATANG SERAI - Dwi Saraswati; Yunita Sari Rioni; Ikhah Malikhah; Nura Amalia Afan (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
The implementation of Accounting Information Systems (AIS) and the effectiveness of decision-making play a significant role in enhancing the performance of Micro, Small, and Medium Enterprises (MSMEs). This research aims to examine the influence of AIS and decision-making effectiveness on the performance of MSMEs in Pematang Serai Village, Tanjung Pura District. Using a quantitative method and a saturated sampling technique involving 35 MSMEs, multiple linear regression analysis was conducted to test the relationship between AIS, decision-making effectiveness, and MSME performance. The research findings indicate that the adoption of AIS has a significant positive impact on MSME performance, with MSMEs effectively utilizing AIS more likely to experience increased revenue growth, profitability, and operational efficiency. Furthermore, the effectiveness of decision-making was found to have a positive impact on MSME performance, enabling MSMEs to respond quickly to market changes, identify growth opportunities, and optimize resource allocation. By integrating quantitative and qualitative findings, this study provides a comprehensive understanding of the influence of AIS and decision-making effectiveness on MSME performance in Pematang Serai Village.